2016
DOI: 10.3233/jbr-160117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethylene on ripening of kiwifruit stored under controlled or modified atmosphere packaging and treated with 1-methylcyclopropene

Abstract: BACKGROUND: Kiwifruit (Actinidia deliciosa (A. Chev.) C.F. Liang et A.R. Ferguson cv. 'Hayward') is usually harvested firm, unripe, and with a high starch content, and thus fruit do not always achieve a suitable soluble solid concentration (SSC), and soft texture when ripe. A high dry matter concentration at harvest can be used to predict fruit sweetness at ripening. However, fruit softening capacity is difficult to predict because of the interaction between postharvest practices and biochemical processes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…At 30 d, the pulp of the combined treatment group showed slight rotting, and the peel did not deteriorate significantly. Zoffoli et al [20] research with kiwifruits shows that both 1-MCP and MAP reduced fruit softening after 60 and 90 days at 0°C and delayed fruit ripening at 20°C. And MA combined with 1-MCP binding effectively inhibited the occurrence of pomegranates chilling injury [32], Studies by Maalekuu et al [33] with bell peppers showed strong correlation between weight loss and fruit softening and general fruit appearance.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…At 30 d, the pulp of the combined treatment group showed slight rotting, and the peel did not deteriorate significantly. Zoffoli et al [20] research with kiwifruits shows that both 1-MCP and MAP reduced fruit softening after 60 and 90 days at 0°C and delayed fruit ripening at 20°C. And MA combined with 1-MCP binding effectively inhibited the occurrence of pomegranates chilling injury [32], Studies by Maalekuu et al [33] with bell peppers showed strong correlation between weight loss and fruit softening and general fruit appearance.…”
Section: Discussionmentioning
confidence: 98%
“…e combined treatment of MA and 1-MCP significantly prolonged the shelf life of basil leaves [19]. And a synergistic effect of 1-MCP and MA extended the kiwifruit's storage life to 120 days at 0°C [20]. Li [17] found that 1-MCP plus microperforated film packaging is the most effective preservation method for "Laiyang" pear fruit, which maintains the firmness, color, titratable acidity, and vitamin C content of the fruit flesh.…”
Section: Introductionmentioning
confidence: 99%
“…In yet another study, it was reported that, although 1‐MCP (50–1000 nL L –1 ), applied at the color break stage (25% yellow), delayed softening and the disease incidence of treated papaya, it produced ‘rubbery’ fruit pieces, possibly as a result of the low recovery of ethylene biosynthesis . The length of storage and 1‐MCP treatment may prevent ethylene biosynthesis as has been reported for 1 µL L –1 24‐h treated kiwifruit stored for 60 days and 90 days at 0 °C . This may impact on texture quality and palatability when used as a cut product.…”
Section: Impact Of Postharvest Handling Of Raw Materials On Cut Producmentioning
confidence: 94%
“…The fruit were stored in an ethylene-free environment produced by passing the incoming air stream through a potassium permanganate (Bioconservacion, BCN, Spain) ethylene scrubber. The ethylene concentration was monitored every 2 days, maintaining ethylene concentrations consistently at <0.005 ml liter −1 (Zoffoli et al 2016). Stem end rot incidence was expressed as the percentage of diseased fruit.…”
Section: Methodsmentioning
confidence: 99%